Tingkat pengetahuan ibu tentang pemantauan gerakan janin pada ibu hamil dengan preeklampsia - Fitri Yani; Dian Roza Adila; Riau Roslita (Universitas Ahmad Dahlan, 2021)
Preeclampsia is a pregnancy complication that can cause fetal and maternal morbidity and mortality. One way that pregnant women can reduce the risk of pregnancy complications is by monitoring the fetus's movement. The mother must know about monitoring fetal movements by analyzing fetal movements. The mother can detect the health of the fetus from an early stage. This study aims to determine the level of knowledge about monitoring fetal movement in pregnant women with preeclampsia. This quantitative research uses a simple descriptive design. The study's location is in the inpatient room of Teratai 1 and the Arifin Ahmad Hospital's obstetrics department, Riau Province. The population is 85 people. The selected sample amounted to 46 people with accidental techniques. The data was collected using a questionnaire and then analyzed univariately. The study found that 80.4% of pregnant women lacked knowledge about monitoring fetal movements. Pregnant with preeclampsia need to pay more attention to their fetal movements by seeking more information from health services and other sources, such as social media. Lack of monitoring of fetal movements and maternal knowledge about it causes fetal and maternal mortality rates to be challenging to reduce. Therefore, health workers must be more active in educating about pregnant women's health problems with preeclampsia to achieve the SDGs target in reducing infant and maternal mortality.